MRI capture of intermittent ventriculomegaly in a patient with ventriculo-peritoneal shunt. (3rd September 2017) - Aly, Ahmed; El-Beshlawi, Ismail; Howarth, Simon; Smith, Stuart
Abstract: Intermittent change in ventricular size in patients with ventriculo-peritoneal shunts is a recognised complication but definitive imaging evidence is rare. We report a 3 years old boy with a medullary astrocytoma and ventriculo-peritoneal shunt placement who demonstrated intermittent ventriculomegaly during a single MRI scan.